Intersections of Personal Assistance Services for Rural Disabled People and Home Care Workers' Rights - Sage, Rayna; Standley, Krys; Mashinchi, Genna M. (Frontiers in Rehabilitation Sciences, 2022)
It is very difficult to find and keep workers to provide home-based care for disabled people, especially in rural places. There is a tension between the rights of disabled people and the rights of home-based personal care workers In this brief review, we explore the intersections of historical and social forces that shaped federal-level policies for both disability rights and the rights of personal care workers, as well as the current state of the policies.. This paper provides a narrow focus on federal policies relevant to both groups while also considering how the urbancentric nature of advocacy and policy making has failed to address important issues experienced by rural people. In addition to briefly reviewing relevant federal policies, we also explore sources of support and resistance and the role of ableism and sexism in addressing the sometimes competing needs. We conclude with recommendations for how to better address the needs of rural people with disabilities using home-based personal care services and the workers who provide them.